2020
DOI: 10.23947/2334-8496-2020-8-3-83-92
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Mathematics Study Strategies of Secondary School Students From the Perspective of Multiple Variables

Abstract: The academic achievement of students can decrease if they fail to use mathematics study strategies well. This situation may lead to negative opinions and attitudes among students towards mathematics. In this study, it was aimed to examine the mathematics study strategies of students enrolled at secondary schools in terms of academic achievement and multiple variables. Relational survey method, one of the quantitative research methods, was used to obtain the data. The universe of the study consists of a total o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…However, the first subject could not relate the concept of a circle area, and the second subject could not determine the right strategy to solve the problem even though it had used the concept of a circle area. They have not performed well in their mathematics study skills which causes them to be unable to apply the right strategy (Arifin, Zulkardi, Putri, & Hartono, 2021;Tezer et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the first subject could not relate the concept of a circle area, and the second subject could not determine the right strategy to solve the problem even though it had used the concept of a circle area. They have not performed well in their mathematics study skills which causes them to be unable to apply the right strategy (Arifin, Zulkardi, Putri, & Hartono, 2021;Tezer et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, slow learners are identified as children who have IQs in the range of 70-85 (Kaznowski, 2004) or the range of 75-89 (Malik, Rehman, & Hanif, 2012), so it can be concluded that IQs of slow learners are in the range of 70-90 (Krishnakumar, Jisha, Sukumaran, & Nair, 2011). Therefore, it gives slow learners the inability to keep up with academic demands (Kaznowski, 2004) and encounter troubles in learning (Tran, Tuyen, Trinh, & Tai, 2019), thus leading to low achievements, which in turn does not make them well performed in their mathematics study skills (Tezer, Cumhur, & İldırımlı, 2020).…”
Section: Introductionmentioning
confidence: 99%